Zeus : king of the gods - O'Connor, George (O'Connor, George. Olympians, 2010)
Terrified of being killed by one of his children, Kronos devours each of his offspring in turn. Only Zeus, the youngest, is saved. Though raised to enjoy a life of leisure, Zeus must fulfill his destiny and lead a new race of gods--and he must begin by destroying his own father.